2015
DOI: 10.1016/j.apcatb.2014.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Surface decoration of commercial micro-sized TiO2 by means of high energy ultrasound: A way to enhance its photocatalytic activity under visible light

Abstract: Highlights Surface decoration of micro-sized TiO 2 by means of high-energy ultrasound AbstractAlthough the TiO 2 is one of the most promising materials for its photocatalytic potential related to the pollution abatement, it strongly suffers from the low photocatalytic activity if it is used under visible light and not under UV light. Among the various possible modifications, the surface decoration with metal or metal oxides NPs can be a good strategy to increase the potential of TiO 2 in the visible range. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 30 publications
(38 reference statements)
0
17
0
1
Order By: Relevance
“…Metallic copper nanoparticles have been exploited to decorate TiO 2 and to investigate the photocatalytic degradation of gaseous acetone and acetaldehyde under visible LED irradiation (400-700 nm). The authors reported a 27% degradation for acetone and 16% degradation for acetaldehyde after 6 h of irradiation [142,143].…”
Section: Photocatalytic Degradation Of Vocsmentioning
confidence: 99%
“…Metallic copper nanoparticles have been exploited to decorate TiO 2 and to investigate the photocatalytic degradation of gaseous acetone and acetaldehyde under visible LED irradiation (400-700 nm). The authors reported a 27% degradation for acetone and 16% degradation for acetaldehyde after 6 h of irradiation [142,143].…”
Section: Photocatalytic Degradation Of Vocsmentioning
confidence: 99%
“…Further, fixing the Mn amount to 20%, the pH of the suspension changed from the spontaneous value (around pH 4) to both acidic (pH 3) and alkaline (pH 9, 12) by addition of HCl and KOH, respectively. The solvent evaporation procedure and the heating treatment were the same as previously reported [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…The starting pollutant concentration was 400 ppm. The photodegradation reaction was performed in a four openings PIREX glass reactor of 5 L. A gas chromatograph (Agilent 3000 A Micro-GC, Santa Clara, CA, USA), directly connected to the reactor, monitored the internal concentration of the organic molecule, as well as of any by-products and CO 2 , as reported in our previous work [ 24 ]. Two different irradiation sources, a UV lamp (HG 500 Jelosil SRL, 315–400 nm and irradiation intensity of 30 W m −2 , Milan, Italy) and an LED one (MW Mean Well, 400–700 nm, 350 mA, 16.8 W and irradiation intensity of 15,000 lx, to simulate the visible light, Taiwan, China) were used.…”
Section: Methodsmentioning
confidence: 99%
“…The artificial lighting in the most part of the indoor environments is achieved with LED lamps, without any contribution of UV irradiation. Concerning this, many studies on the commercial micro-sized powders show that, modifying TiO 2 , it is possible to make it photoactive even to the visible wavelengths [62,63]. This is very promising for a future application on porcelain grés tiles and for their application in the indoor environments lit by LED lights.…”
Section: Photocatalytic Active Tilesmentioning
confidence: 99%